Answer:
![f^(\prime)(x)=3(\sin x+x\cos x)e^(3x\sin x)](https://img.qammunity.org/2023/formulas/mathematics/college/8qrtex8vvga2v6vo9zqlpklde3srhhh5f7.png)
Step-by-step explanation:
Given the function
![f(x)=e^(3x\sin x)](https://img.qammunity.org/2023/formulas/mathematics/college/5r8tr8dinz3her8izddiqbb4k4zttpc81u.png)
f'(x) represents the first derivative of f(x) with respect to x.
This can be done by using the principle of function of a function.
Let u = 3x sinx
Then
f'(x) = f'(u).u'(x)
![\begin{gathered} f(u)=e^u \\ f^(\prime)(u)=e^u \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/uchp10bj5xd4qu6z9jtd56rimbaz3wlwl2.png)
![\begin{gathered} u(x)=3x\sin x \\ u^(\prime)(x)=3\sin x+3x\cos x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/u9zx52i4ief5yzb532608ue0255zgtpsed.png)
Therefore;
![f^(\prime)(x)=e^u.(3\sin x+3x\cos x)](https://img.qammunity.org/2023/formulas/mathematics/college/8sjb8exp7683p5mjiijfusng0t0ikwfjmb.png)
with u = 3x sinx, we have
![\begin{gathered} f^(\prime)(x)=(3\sin x+3x\cos x)e^(3x\sin x) \\ \\ =3(\sin x+x\cos x)e^(3x\sin x) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qou7807bywktnx90244y9mmexwo3cvr6o2.png)